Collaboration-Based Village Service Innovation in Sabak Auh District, Siak Regency - Adianto, Adianto; Habibie, Dedi Kusuma; Putri, Risky Arya; Indry, Indry; Utami, Ayu Tri (Journal of Governance, 2024)
The research was conducted with the aim of comprehensively analyzing collaborative innovation in village development in Sabak Auh District, Siak Regency. Because the village is the foremost government agent in carrying out development, therefore the village is the foremost gate of development for a country. Therefore, in implementing village development, it must collaborate with all stakeholders to develop the innovations that have been determined. Because building villages with a collaboration, empowerment, and innovation approach focuses on exploring and developing the potential of the village based on local wisdom, which will become the spirit to realize an independent village. This fact is an investment in the future that will accelerate welfare for village communities more evenly in the long term. The research found that there are several innovations that have been made in village development in the Sabak Auh Sub-district, Siak Regency. The implementation of these innovations includes the implementation of a digitalization program through applications launched by the Siak District government, such as the “Si Cantik ‘ and ’Smart Kampung” applications. The implementation of collaborative innovation in village development in Sabak Auh Subdistrict, Siak Regency, is still running in a limited manner and is not fully optimized, and the factors causing the failure of collaborative innovation in village development in Sabak Auh Subdistrict, Siak Regency, are (1) the application of village service innovations that are not good and (2) training on the use of innovations that have not been maximized.